Revolutionizing Retail: The Role of Augmented Reality-Driven Information Systems in Enhancing Customer Experience and Engagement - Raymond-Paul,James Daniel; De Sousa,Jordina (2025)
Augmented reality (AR) is increasingly being adopted in fashion retail to enhance customer ex-perience, boost engagement, and reduce uncertainty in online shopping environments. While AR offers both hedonic and utilitarian value, its implementation across large multinational fashion companies remains inconsistent due to financial, technological, and organizational barriers. This study investigates how Augmented Reality-driven information systems can be strategically im-plemented to improve customer engagement and experience in retail environments. A qualitative, interpretivist approach was used, combining semi-structured interviews with professionals and open-text surveys to explore the perceptions, challenges, and outcomes of AR adoption. The-matic analysis revealed five key themes, including current use cases, customer motivation, barri-ers to adoption, decision-making support, and future outlooks. The study also introduces a Stra-tegic AR Implementation Framework to guide retail organizations in aligning AR technologies with enterprise systems and customer needs. While the findings confirm key patterns in existing literature, they also highlight gaps related to system readiness, user resistance, and integration challenges. The research concludes that AR’s value lies not only in its novelty but in its ability to deliver measurable outcomes through thoughtful, context-sensitive implementation. Future research is recommended to explore AR in other sectors and in combination with emerging technologies.
Keywords: Augmented Reality (AR); Fashion Retail; Customer Engagement; Customer Experience; Information Systems (IS); Digital Transformation; AR Implementation; Virtual Try-On; Mobile AR; Retail Innovation